Pengaruh Pendampingan Orang Tua dalam Menggosok Gigi terhadap Skor OHIS pada Anak Usia 6-7 Tahun - Nur Aida, Wanda; Widyastuti, Nugraheni; Afandy, Afif (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2022)
Health that needs to be considered in addition to general body health, namely dental and oral health. Efforts to maintain dental and oral health in children require parental assistance. Parents' assistance inbrushing their teeth is expected to have a positive impact on reducing children's OHIS scores. The aim of this study was to determine the effect of parental assistance in brushing their teeth on the OHIS score in children aged 6-7 years. This research is an experimental study with a One Group Pretest-Posttest Design. The population in this study were students of SDN 01 Panjang Wetan 01 Pekalongan, totaling 100 students. The sample used was 50 samples with purposive sampling technique. Analysis was performed by univariateanalysis (frequency distribution) and bivariate analysis using the Wilcoxon test. The results showed that therewas a significant difference in children's OHI-S scores before and after assisting parents in brushing their teeth, p-value <0.05. So it can be concluded parental assistance will affect the condition of dental and oral hygiene (OHI-S) in children.